Formononetin Treatment in Type 2 Diabetic Rats Reduces Insulin Resistance and Hyperglycemia - Oza, Manisha J.; Kulkarni, Yogesh A. (Frontiers in Pharmacology, 2018)
Type 2 diabetic mellitus is a multifactorial metabolic disorder affecting huge population around the world. This indicates that there is an urgent unmet need of cost effective, new treatment strategies for type 2 diabetes mellitus with no or less side effects. Phenolic compounds including isoflavones are known for their beneficial effect in metabolic disorders. The present work was intended to find out efficacy of formononetin, an isoflavone treatment in experimental model of type 2 diabetes. Type 2 diabetes mellitus was induced by feeding high fat diet for two weeks prior to streptozotocin administration in Sprague Dawley rats. Diabetic animals were treated with formononetin for 28 days at three dose level i.e. 10, 20 and 40 mg/kg body weight orally. The effect of formononetin treatment on various parameters such as plasma glucose, glucose tolerance, insulin, HOMA-IR, lipid profile, hepatic glycogen content, glycohaemoglobin and SIRT1 expression in pancreatic tissue was measured. Histopathological changes in pancreatic tissue were also studied. Results of the study demonstrate that formononetin treatment reduces blood glucose level significantly (p < 0.001) at all the three dose level. It also improved glucose tolerance, insulin sensitivity and lipid profile along with reduction in glycohaemoglobin content in blood. Formononetin treatment also improved hepatic glycogen level profoundly in diabetic rats. Determination of SIRT1 expression in pancreatic tissue by immunohistochemical analysis showed that formononetin treatment increases the expression of SIRT1 in pancreatic tissue. Histopathological study showed that treatment with formononetin protects pancreatic beta cells from necro-degeneration and atrophic effect. It can be concluded that formononetin treatment reduces insulin resistance and attenuate hyperglycemia in type 2 diabetes which may be due to increasing expression of SIRT1 in pancreatic tissues.